ChemInform Abstract: General Approach to Nitrogen‐Bridged Bicyclic Frameworks by Rh‐Catalyzed Formal Carbenoid Insertion into an Amide C—N Bond. Issue 9 (February 2016) - Harada, Shingo; Kono, Masato; Nozaki, Tomoyuki; Menjo, Yasuhiro; Nemoto, Tetsuhiro; Hamada, Yasumasa
Abstract: The Rh‐catalyzed formal carbenoid insertion into an amide C—N bond delivers azabicyclo[X.Y.Z.]alkane derivatives in good to high yields and proceeds via the formation of Rh‐associated N‐ylides, followed by an acyl group‐selective Stevens [1, 2]‐shift through a concerted addition/elimination process on the sp 2 ‐hybridized carbon.